(untitled) (Nóema, 2019)
In the current evolutionary debate, the «Baldwin Effect» is increasingly mentioned. The aim of this article is to teoretically analyze the original form of this concept, initially called “organic selection”, through the thought of one of its main advocates: James Mark Baldwin. His evolutionary observations, almost forgotten in Modern Synthesis’s refolmulations of «Baldwin Effect», appear widely original in view of contemporary attempt to «extend» the darwinian paradigm.